Resolving out-of-vocabulary words during machine translation - Hassan Awadalla, Hany (2012)
Some implementations provide techniques and arrangements to perform automated translation from a source language to a target language. For example, an out-of-vocabulary word may be identified and a morphological analysis may be performed to determine whether the out-of-vocabulary word reduces to at least one stem. If the out-of-vocabulary word reduces to a stem, the stem may be translated. The translated stem may be inflected if the out-of-vocabulary word is inflected. If the out-of-vocabulary word has any affixes, the affixes may be translated. In some cases, the translated affixes may be reordered before being combined with the inflected and translated stem. If the out-of-vocabulary word is misspelled, the spelling of the out-of-vocabulary word may be corrected before performing the morphological analysis. If the out-of-vocabulary word is a colloquial form of a formal word, the out-of-vocabulary word may be replaced with the formal word before performing the morphological analysis.
US8990066B2 US Grant